Enhancing MCDM with q-rung orthopair fuzzy Dombi generalized Heronian mean / Muhammad Mukhlis Kamarul Zaman, Zahari Md Rodzi and Yusrina Andu - Kamarul Zaman, Muhammad Mukhlis; Md Rodzi, Zahari; Andu, Yusrina (Universiti Teknologi MARA, Perak, 2025)
This paper presents a set of Dombi generalized Heronian mean operators for q-rung orthopair fuzzy numbers (qROFNs) and proposes a multi-criteria decision-making (MCDM) method based on these operators. The operational rules of qROFNs, grounded in the Dombi t-conorm and t-norm, are presented. A q-rung orthopair fuzzy Dombi generalized Heronian mean (qROFDGHM) operator is formulated based on these principles. A method for addressing MCDM problems utilizing qROFNs and the developed operators is proposed. A comprehensive mathematical proof of the operator's idempotency condition, as well as its monotonicity and boundedness properties, validates its theoretical basis. When addressing MCDM challenges, the proposed operator generates effective outcome solutions by leveraging membership and non-membership degree interactions. The qROFDGHM operator has a better ability to handle imprecise, uncertain, and conflicting data when compared with existing methods. This study contributes to fuzzy decision-making advancement through its development of a flexible theoretical aggregation operator.